Sports Massage Service for Central Java Pencak Silat Regional Training Athletes in Efforts to Reduce Pain and Maximize Recovery After Intense Training - Rony Syaifullah; Abdul Aziz Purnomo Shidiq (Universitas Lambung Mangkurat, 2024)
Pencak Silat is a traditional sport that requires intense training to achieve maximum performance. Central Java's Pencak Silat Regional Training athletes undergo intensive training, often resulting in injuries. Injuries occur due to poor physical recovery and the absence of therapists to expedite the recovery process. Group 142 students from the UNS MBKM Community Service program established a Sports Massage Service to accelerate recovery after intense training. This program was implemented at the Central Java Pencak Silat Regional Training Athlete dormitory in Semarang, Central Java, specifically in Patemon village, Gunung Pati district. The service aims to provide massage services that can alleviate muscle fatigue, reduce pain, decrease the risk of injury, and maximize recovery. The method used is Asset Based Community Development (ABCD). The service involved direct observation of 11 athletes and interviews with coaches. The results indicated a reduction in the average pain intensity from 5.64 to 2.73, with an average decrease of 2.91. The figure of 2.91 indicates that the pain is in the mild category. The impact of this service is reduced pain and more optimal recovery for the Central Java Pencak Silat Regional Training athletes in preparation for the Adult National Championship Pre-National Sports Week (PON). The results of this activity demonstrate that the sports massage service is effective in maximizing recovery and reducing pain after intense training.